The Power of Linear Methods in Determining the Dominant Fiscal Regime: A Research on Turkiye - Masatci, Kaan; Oktayer Buzluca, Asuman (ISTANBUL UNIV, METHODOLOGY & SOCIOLOGY RESEARCH CENTER, 2022)
The Fiscal Theory of the Price Level suggests that in a non-Ricardian regime, an inflation targeting monetary policy will no longer be able to control the price level, and that optimum policy should always include a combination of monetary and fiscal policies. The aim of this paper is to investigate the dominant fiscal policy regime in Turkiye using the ARDL Bounds Testing Approach and to compare the results with actual observations. The review period covers 1996-2019 period for which the quarterly data set is used. Based on the assumption that the actual behavior of the government's fiscal policy can be observed more accurately with the structural balance, the sub-components of primary balance (structural and cyclical balance) are also included in the analysis. During the review period, there were important breaks in the Turkish economy that could lead to changes in monetary and fiscal policies. To observe possible policy changes, rather than dividing the sample into different periods, dummy variables were used to reflect the difference between periods. The results of the analysis show that the structural balance more accurately reflects the actual behavior of the government's fiscal policy. Another finding is that the linear ARDL approach is insufficient to capture the changes in the fiscal policy, especially in the periods when the fiscal space narrows.
Keywords: The Fiscal Theory of the Price Level; Structural Budget Balance; Ricardian non-Ricardian; ARDL; PRICE-LEVEL; MONETARY; POLICY; Sociology